Children for Social Justice - McCrossin, Jeff (First Peoples Child & Family Review, 2012)
It is often assumed that children lack the developed capacity to understand complicated political issues (for example, Arendt, 1959; Pearce, 2011; and Warmington, 2012a, 2012b). This assumption is contested through a review of the literature examining adult conceptions the child, and children’s rights to political participation, citizenship, and direct representation (Steffler, 2009; Wall & Dar, 2011; Wyness, Harrison, & Buchanan, 2004). A variety of historical and contemporary examples of children engaging in social justice campaigns and movements are provided (Elshtain, 1996; Milstein, 2010; Smith, 2012; Traubman, 2005; Bergmar, 2010). A potential means for supporting children in social justice engagement is explored through social justice education (Dover, 2009; Kelly & Brooks, 2009).